The influence of coolant scale deposit inside the internal combustion engine on the piston and cylinder deformations - G. Garbinčius (Transport, 2005)
This paper presents the analysis of the influence of engine coolant scale deposits on the deformations in the piston – cylinder pair. The results of carried out calculations enable to make more precise evaluation of cylinder repair dimensions. The aim of calculations was to establish how the thermal gap between the piston and cylinder varies in accordance with variations of heat transfer conditions, i.e. when on the outer surface of the cylinder a layer of scale deposits is formed.